2022
DOI: 10.3847/1538-4357/ac90bd
|View full text |Cite
|
Sign up to set email alerts
|

Drift Rates of Narrowband Signals in Long-term SETI Observations for Exoplanets

Abstract: The Doppler shift of a radio signal is caused by the relative motion between the transmitter and receiver. The change in frequency of the signal over time is called the drift rate. In the studies of radio search for extraterrestrial intelligence (SETI), extraterrestrial narrowband signals are expected to appear “chirped” since both the exoplanet and Earth are moving. Such planet rotation and orbital revolution around the central star can cause a nonzero drift rate. Other relative motions between the transmitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…According to Tao et al (2022), the value of MDR depends on the observed frequency band because the drift rate is proportional to the transmitted frequency of the signal. For FAST L-band, we set the MDR to 4 Hz s −1 , which is large enough to search for signals transmitted from a typical planet in a habitable zone (Li et al 2022;Tao et al 2022). TurboSETI outputs the best-fit frequency, drift rate, and S/N of the hits to a .dat file.…”
Section: Discussionmentioning
confidence: 99%
“…According to Tao et al (2022), the value of MDR depends on the observed frequency band because the drift rate is proportional to the transmitted frequency of the signal. For FAST L-band, we set the MDR to 4 Hz s −1 , which is large enough to search for signals transmitted from a typical planet in a habitable zone (Li et al 2022;Tao et al 2022). TurboSETI outputs the best-fit frequency, drift rate, and S/N of the hits to a .dat file.…”
Section: Discussionmentioning
confidence: 99%
“…According to Tao et al (2022), the value of MDR depends on the observed frequency band because the drift rate is proportional to transmitted frequency of the signal. For FAST L-band, we set the MDR to 4 Hz/s, which is large enough to search for signals transmitted from a typical planet in habitable zone (Li et al 2022;Tao et al 2022). TurboSETI outputs the best fit frequency, drift rate, and S/N of the hits to a DAT file.…”
Section: Discussionmentioning
confidence: 99%
“…However, this process relies on a fully representative library of simulated ETI signals, including more possible patterns of birdies. For example, the pattern may be different for different brightness, drift rate (e.g., Li et al 2022), and relative position to the beams. Some interesting candidates may be missed (removed with RFI) because there is no kind of birdie that could guide our parameter selection.…”
Section: Discussionmentioning
confidence: 99%